2022
DOI: 10.1136/tobaccocontrol-2021-056876
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of tax policy changes in Montenegro: smoking behaviour by socio-economic status

Abstract: BackgroundThe main goal of this study was to examine the responsiveness of smoking prevalence and cigarette consumption to price and income changes by income groups and the effectiveness of tax policy changes to reduce cigarette consumption in Montenegro.Data and methodsA two-part model was applied to estimate smoking participation, smoking intensity price and income elasticity. The first part of the model applies logit regression, while the second uses Deaton’s model to improve the validity and objectivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
(51 reference statements)
1
4
1
Order By: Relevance
“…The smoking rate did not decrease as much in the youngest group (aged 15-24 years) as in the other age groups. This result is inconsistent with many studies conducted in other countries indicating that price policies significantly affected the smoking rate among young people (Cizmovic et al, 2022;Nikaj & Chaloupka, 2014;Sweis & Chaloupka, 2014). However, this result is consistent with a previous study conducted in Thailand, which indicated that friends were the primary source of cigarettes among young people (Hammond et al, 2008).…”
Section: Discussioncontrasting
confidence: 95%
“…The smoking rate did not decrease as much in the youngest group (aged 15-24 years) as in the other age groups. This result is inconsistent with many studies conducted in other countries indicating that price policies significantly affected the smoking rate among young people (Cizmovic et al, 2022;Nikaj & Chaloupka, 2014;Sweis & Chaloupka, 2014). However, this result is consistent with a previous study conducted in Thailand, which indicated that friends were the primary source of cigarettes among young people (Hammond et al, 2008).…”
Section: Discussioncontrasting
confidence: 95%
“…One study, rated at moderate risk of bias, found that households in Bosnia and Herzegovina with lower total expenditures were more responsive to cigarette prices, with differences large enough to be economically meaningful [ 63 ]. Another study, rated at serious risk of bias, found that low- and middle-SES households were more responsive to price than high-SES households in Montenegro [ 62 ]. A third study, rated at critical risk of bias, found some statistically significant socioeconomic differences in price responsiveness for cigarette/bidi smoking initiation in India; differences, however, were very small and unlikely to be meaningful [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the most important limitation was the lack of formal assessment of socioeconomic differences in price responsiveness. Only seven of 32 studies formally assessed statistically whether own-price effects were modified by SES; three used interactions [ 38 , 39 , 46 ] while four used seemingly unrelated regressions to conduct Wald tests of equality of coefficients across equations [ 33 , 57 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The papers included in this supplement span the regions of Asia, Latin America, and Southeastern Europe. The research focuses on consumer responses to cigarette price increases (Divino et al, 14 Nguyen et al, 15 Vladisavljevic et al 16 ) as well as their distributional impacts (Cruces et al, 17 Gligorić et al, 18 Divino et al, 19 Cizmovic et al, 20 Nguyen et al 15 ). Two papers analyse tax leakages along the tobacco supply chain: Vladisavljevic et al 16 use data from a primary survey in the Southeastern European region to analyse determinants of tobacco tax evasion and Drope et al examine the regional implications of the tobacco value chain in Paraguay.…”
Section: Editorialmentioning
confidence: 99%